(untitled) (Journal of the College of Basic Education, 2025)
The research aimed to prepare static activity exercises supported by assistive devices and to identify the effect of static exercises supported by assistive devices on improving coordination abilities and learning some futsal skills. A community of third-year female students in the Department of Physical Education and Sports Sciences at Ashur University College for the academic year (2024-2025) was identified. The research community numbered (40) male and female students, while the research sample numbered (20) female students, with the sample percentage being (50%) of the original community. The research sample was randomly divided into two groups: the first experimental group (the equipment group), which numbered (8) female students, and the second experimental group (the coordination exercises group), which numbered (8) female students, ranging in age from (18-20) years, in addition to (4) female students to conduct the exploratory experiment. The researcher then proceeded to conduct the pre-test and prepare units. The study included static activity exercises and assistive devices, while the control group remained in its conditions, following the instructor’s approach. After implementing the research experiment, the researcher conducted a post-test. She then relied on the statistical package to extract the results, which led to the most important conclusions, including: Static activity exercises supported by assistive devices improve students’ coordination abilities and skill learning in futsal, leading to improved overall performance on the field. One of the most important recommendations is to emphasize the implementation of static activity exercises supported by assistive devices as an essential part of the training curriculum to improve the educational and training experience for students in futsal.